2009
DOI: 10.1038/nnano.2009.227
|View full text |Cite
|
Sign up to set email alerts
|

Uniform exciton fluorescence from individual molecular nanotubes immobilized on solid substrates

Abstract: Uniform exciton fluorescence from individual molecular nanotubes immobilized on solid substrates Eisele, Doerthe M.; Knoester, Jasper; Kirstein, Stefan; Rabe, Juergen P.; Vanden Bout, David A.; Rabe, Jürgen P. Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.Downloaded from the University of Groningen/UMCG research database (Pure): http://www.rug.nl/research/portal. For technic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
236
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 210 publications
(247 citation statements)
references
References 30 publications
8
236
1
2
Order By: Relevance
“…22 This perspective motivates many of the recent studies of the optical absorption and luminescence properties of the collective exciton states in these systems, as well as the energy transport and relaxation caused by these states. [2][3][4][5][6][7][23][24][25][26][27] In homogeneous cylindrical aggregates, the rotational symmetry around the axis imposes strong optical selection rules on the wave number k 2 that characterizes the exciton's Bloch wave function along a ring around the cylinder. In particular, it is easily shown that only states with k 2 = 0 and k 2 = ±1 may carry optical oscillator strength.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…22 This perspective motivates many of the recent studies of the optical absorption and luminescence properties of the collective exciton states in these systems, as well as the energy transport and relaxation caused by these states. [2][3][4][5][6][7][23][24][25][26][27] In homogeneous cylindrical aggregates, the rotational symmetry around the axis imposes strong optical selection rules on the wave number k 2 that characterizes the exciton's Bloch wave function along a ring around the cylinder. In particular, it is easily shown that only states with k 2 = 0 and k 2 = ±1 may carry optical oscillator strength.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] Examples of molecules that in solution self-assemble into aggregates of a tubular shape are carbocyanine molecules with hydrophobic and hydrophilic side groups [2][3][4][5][6][7] and porphyrin derivatives. [8][9][10][11][12] Both these molecules yield aggregates with a diameter of the order of 10 nm and a length of up to microns, which explains why they are often referred to as molecular nanotubes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a water−methanol mixture, C8S3 monomers self-assemble into nanotubes with an outer wall diameter of ∼12.5 nm, an inner wall diameter of ∼6 nm, and longitudinal dimensions tens of micrometers in length (panels b and d of Figure 1). 13,16 To accomplish our study, we have developed a method to stabilize C8S3 LHNs against light-induced and cryogenic damage in a sugar-based matrix. 19 We modify the normal preparation by diluting the aggregate preparation in a highly concentrated sucrose−trehalose solution and drying overnight to create a concentrated, clear, dry, sugar-glass matrix ( Figure 1c).…”
mentioning
confidence: 99%
“…J-aggregate nanotubes are attractive for efficient electron transfers because they share the molecular packing feature with photosynthetic light-harvesting antennas [19]- [24]. In this paper, we report the formation of templated J-aggregate nanotubes by the adsorption of 3,3'-diethylthiacarbocyanine iodide (DTCC) on the self-assembled nanotubes of lithocholic acid (LCA).…”
Section: Introductionmentioning
confidence: 99%